2016
DOI: 10.1126/scisignal.aaf5106
|View full text |Cite
|
Sign up to set email alerts
|

MET signaling in keratinocytes activates EGFR and initiates squamous carcinogenesis

Abstract: The receptor tyrosine kinase MET is abundant in many human squamous cell carcinomas (SCCs), but its functional significance in tumorigenesis is not clear. We found that the incidence of carcinogen-induced skin squamous tumors was substantially increased in transgenic MT-HGF (mouse metallothioneinhepatocyte growth factor) mice, which have increased abundance of the MET ligand HGF. Squamous tumors also erupted spontaneously on the skin of MT-HGF mice that were promoted by wounding or the application of 12-O-tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 92 publications
2
25
1
1
Order By: Relevance
“…Signaling downstream from oncogenic RAS is dependent on an intact EGFR in mouse keratinocytes. 10 Accordingly, in the genetic model, tumor growth was consistently impaired by the absence of EGFR in tumor epithelium ( Fig. 1a).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Signaling downstream from oncogenic RAS is dependent on an intact EGFR in mouse keratinocytes. 10 Accordingly, in the genetic model, tumor growth was consistently impaired by the absence of EGFR in tumor epithelium ( Fig. 1a).…”
Section: Resultsmentioning
confidence: 91%
“…Both groups were transformed with a constitutively active form of HRAS that is expressed equally in both genotypes (Suppl Fig.1a). Signaling downstream from oncogenic RAS is dependent on an intact EGFR in mouse keratinocytes 10 . Accordingly, in the genetic model, tumor growth was consistently impaired by the absence of EGFR in tumor epithelium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We did not reproduce spontaneous breast or thyroid cancers, but the systematic pathologic study found lymphocytic thyroiditis in 14 of 23 transgenic mice when, in patients, chronic lymphocytic thyroiditis is associated with a 2-fold increased risk of papillary thyroid cancer (39). In addition, one of the transgenic mice developed a skin squamous cell carcinoma of the ear, as observed in mice transgenic for HGF with a strong activation of the MET pathway (40). We reproduced experimentally the occurrence of skin carcinomas in our transgenic mice, and reduced significantly the number of cancers by concomitant administration of a MET inhibitor demonstrating that MET activation is sufficient for increasing the susceptibility to skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that directly targeting MET, EGFR, or ERBB2 was sufficient to impact cSCC cell viability (Figure 3c). MET and EGFR/ERBB2 signaling pathways can contribute to driving cSCC development, and a subset of cSCCs respond to EGFR inhibitors (Cataisson et al, 2016;Harwood et al, 2016;Mellerio et al, 2016). Suppression of USP8 could provide a means to simultaneously interfere with multiple therapeutically relevant receptors, which could overcome resistance because of receptor redundancy or cross-talk.…”
Section: Usp8mentioning
confidence: 99%